From Trauma to Triumph: A Successful Outcome of Intraocular Foreign Body: Poster Presentation - Case Report - Resident - Primasakti, Pattih; Helvanda, Weni (Majalah Oftalmologi Indonesia, 2023)
Introduction : Intraocular foreign body (IOFB) is a medical condition characterized by the presence of a foreign object within the eye. IOFBs can cause significant damage to the eye, leading to vision loss, ocular inflammation, and even blindness. Case Illustration : We present a case report of a 37-year-old male patient who presented to the emergency department with a history of sudden-onset eye pain and decreased vision in the right eye after a gravel had struck him in the eye while working in a field. Slit-lamp examination revealed a 4mm corneal rupture, iris damage, and traumatic cataract. Computed tomography confirmed the presence of the foreign body in inferonasal quadrant of the retina. The patients underwent vitrectomy and silicone oil tamponade was placed to support the retina. Foreign body had shattered into small pieces and aspirated during vitrectomy. Endolaser photocoagulation was performed to contain the injury site. Lens was removed and iris claw was implanted. Visual acuity improved from hand movement to 20/100. No signs of endophthalmitis, retinal detachment, or other complications were noted during the follow-up period. ultrasound confirmed the absence of foreign body. Discussion : IOFBs is a sight-threatening condition that can result from various occupational or recreational activities, as well as accidental trauma. Depending on the size, shape, and composition of the foreign body, it can cause damage to the cornea, iris, lens, vitreous, and retina, leading to vision loss or permanent visual impairment. Conclusion : The management of IOFBs depends on the location, size, IOFB composition, and severity of ocular trauma. Vitrectomy is an effective approach